2017
DOI: 10.4028/www.scientific.net/aef.23.45
|View full text |Cite
|
Sign up to set email alerts
|

Piezoresistivity in Micro Carbon Fiber Silicone Composites for Electrical Resistance to Strain Sensing

Abstract: In order to develop a cost-effective carbon fiber reinforced polymer sensor for compressive strain monitoring, a study was carried out to assess electrical and piezoelectric properties of samples containing five different carbon fiber weight percentages. Testing focused on sensing ability throughout measurement of resistivity: (1) when submitted to uniaxial variable compressive strain; (2) to time prolonged relaxation at constant strain; (3) and influence of environment temperature on measurements. Results ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Moreover, it has an advantage over contact electrodes regarding thermal behavior compatibility with the composite's polymeric matrix. 16 Measurements of R were made using a two-probe technique, 50 mm apart, measured along the intended operational deformation axis (see Figure 3). The selection of a two-probe electrode design was based on the simplicity of manufacture, as well as considerations in everyday use as a sensing unit when deployed for remote monitoring.…”
Section: Experimental Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, it has an advantage over contact electrodes regarding thermal behavior compatibility with the composite's polymeric matrix. 16 Measurements of R were made using a two-probe technique, 50 mm apart, measured along the intended operational deformation axis (see Figure 3). The selection of a two-probe electrode design was based on the simplicity of manufacture, as well as considerations in everyday use as a sensing unit when deployed for remote monitoring.…”
Section: Experimental Workmentioning
confidence: 99%
“…Research on the R behavior of self-sensing carbon fiber polymer composites (SSCFPC) has shown sensing ability to vary as a function of the weight ratio of micro-carbon fibers in a composite (wt%). Previous analysis by Miguel et al 16 found for wt% up to 13% of micro carbon fiber polymer composites (MCFPC), presented measurements of R with linear decreasing behavior. For wt% above 40% and incorporating approximately five times shorter fibers, R was found to have a linear increasing behavior.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…B and relaxing it to the same preload as in fig.1 C we get a similar change in resistance that follows the load, but with a negative gauge factor. Both resistance change tendencies for B and C seem to decrease as the sample is repeatedly deformed, which previous research hypothesize to be caused by either microcracking, rearrangement of conductive paths or bending of the fibers causing piezoelectric effects [26]. It is clear from the plots that the piezoresistive behavior of the material is not linear, and while some of this, such as additional peaks of increased resistance as the material is being unloaded, might be correlated to Poisson's effect [27] or tunneling [28], making a model for correlating the sensor readings to actual pressure is not novel.…”
Section: Carbon Fibre Silicone Compositesmentioning
confidence: 73%